Towards extracellular vesicle based gene therapy for Huntington's disease - O'Loughlin, A (2016)
Huntington's disease (HD) can be regarded as a model neurodegenerative disorder to screen potential genetic based therapeutics and their carriers. It is an autosomal dominant disorder caused by a mutation in a single gene that leads to progressive neurodegeneration caused in part by protein misfolding. The mutation codes for an expanded polyglutamine tract within the Huntingtin gene (HTT) which leads to neuronal loss through a pathological cascade of events. Current treatment strategies include symptom management but no disease-modifying therapies exist. Research has shown that nucleic acid based therapeutics aimed at decreasing HTT expression can prevent, or reverse, the phenotype. Translating such therapies to the clinic is hindered by the blood brain barrier (BBB) and the lack of an easily administrable, non-toxic, immunologically inert delivery vehicle capable of bypassing the BBB. This study examines a range of nucleic acid based therapeutics for their potency and toxicity, and evaluates extracellular vesicles (EVs) as a delivery vehicle through investigation of the biodistribution of brain targeted EVs and an analysis of EV loading. A small interfering RNA (siRNA) targeting a region upstream of the repeat induced potent non-toxic silencing of HTT. In examining EVs as a carrier for therapeutics for neurological diseases including HD, it was found that targeting can increase brain accumulation of EVs but that the physiological characteristics of EVs which make them susceptible to clearance by the reticuloendothelial system (RES) must be further evaluated to bioengineer modified EVs to avoid fast clearance. Lastly, loading by electroporation was found to induce siRNA aggregation which can lead to overestimation of loading by increasing siRNA content in an ultracentrifugation pellet, but cholesterol-conjugated siRNA mixed with EVs was capable of generating silencing in vitro. This thesis examined EV based treatment for HD through the selection of a nucleic acid cargo to silence HTT, and examination of EVs as a delivery vehicle via biodistribution and loading studies. If the loading can be optimised and fast clearance avoided, there is promise in the use of EVs as a carrier of siRNA for HD.